Perlindungan Hukum bagi Perempuan Ekonomi Lemah dalam upaya Pencegahan Terjadinya Kekerasan dalam Rumah Tangga di Kelurahan Tegalgede Kecamatan Sumbersari Kabupaten Jember - Solehati Nofitasari; Supianto Supianto (JURNAL RECHTENS, 2019)
The household is a small part of a society. A person's goal in fostering a home is to be happy,safe and secure. In realizing this, it depends on each individual in a household, especially inthe attitude, behavior and self-control of everyone in the household. the factors that cause themost domestic violence is caused by economic factors, this is because the Tegalgede Villageis one of the urban areas in the urban area so that the needs are quite a lot but their incomedoes not match the expenditure. This is because their husband's job is only constructionworkers and shop employees. While obstacles in law enforcement in the event of acts ofviolence in the household namely due to violence in the household is still considered a familydisgrace that should not be told or conveyed to other parties. So many victims of domesticviolence, especially women, are reluctant to tell or report violence that has happened to him.Prevention efforts that they do is just to accept the violence that occurred against him.Keywords : Legal Protection, Poor Women, Domestic Violence